2015
DOI: 10.1093/pubmed/fdv080
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of physical activity and sedentary behaviour in the general population in France: cluster analysis with personal and socioeconomic correlates

Abstract: Based on PA and SB, French adults were clustered into groups with socioeconomic differences emphasizing that adapted interventions may be more beneficial for health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
2
37
1
1
Order By: Relevance
“…This mixed pattern has also been observed in previous works [30, 31], as those who report high overall transportation time may have more opportunity of mixing passive and active means. The “active leisure” cluster and “active transportation” cluster presented the highest levels of reported PA (excluding occupational), consistent with previous reports from both US and French cohorts [17, 18]. Cross-sectional and longitudinal studies that investigated the association between leisure and transportation physical activities suggested that higher levels of active transportation are related to higher level of overall and leisure PA and not to a substitution of one context-related activity by another [6, 14, 32].…”
Section: Discussionsupporting
confidence: 90%
“…This mixed pattern has also been observed in previous works [30, 31], as those who report high overall transportation time may have more opportunity of mixing passive and active means. The “active leisure” cluster and “active transportation” cluster presented the highest levels of reported PA (excluding occupational), consistent with previous reports from both US and French cohorts [17, 18]. Cross-sectional and longitudinal studies that investigated the association between leisure and transportation physical activities suggested that higher levels of active transportation are related to higher level of overall and leisure PA and not to a substitution of one context-related activity by another [6, 14, 32].…”
Section: Discussionsupporting
confidence: 90%
“…These two behaviors are in some cases coexistent, and sometimes not. An individual may have both sedentary behaviors and be physically active [2,3]. In this case, PA can moderate but not offset the deleterious effects of sedentary behavior [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no studies analysing the relationship between PF and blood markers together and SES, Omoru et al found that participants with low SES performed occupational PA with higher energy expenditure. Meanwhile, those with high SES performed less occupational PA with less energy expenditure (253). Other authors observed that low SES participants with high occupational PA are also willing to employ time in active-transportation or leisure-time PA (111,343).…”
Section: Discussionmentioning
confidence: 99%
“…Both questionnaires showed significant correlation between them. Cluster analysis is a relative new technique in classifying participants with an important internal validity (hierarchical and non-hierarchical procedure) (253,300). The idea to combine PA and sedentary behaviour is supported because both variables are two different constructs (too much time spend sitting is different from too less time doing PA) (253).…”
Section: Different Classifications From a Clinical And Public Health mentioning
confidence: 99%
See 1 more Smart Citation